Building Values-Based Leadership in the Context of Knowledge Management and Information Technology to Support Sustainable Change in Organizational Culture - Prasetya, Yanto Budi; Az Zaakiyyah, Hizbul Khootimah; Suherlan (PT. LITERASI SAINS NUSANTARA, 2024)
With the continuously evolving business paradigm shifts, organizations need to have the capability to effectively manage knowledge and information technology to understand and respond to environmental changes quickly and accurately. The aim of this research is to formulate recommendations for leaders and managers in building values-based leadership that supports sustainable change in organizational culture, taking into account the aspects of knowledge management and information technology. This research method is a literature review with a qualitative approach that will utilize descriptive analysis. Data is gathered through searches on Google Scholar within the range of 2006-2023. The study's findings indicate that in the era of knowledge and information technology, values-based leadership has become a primary key in shaping sustainable and adaptive organizational culture. Leadership based on moral and ethical values not only sees technology as a tool for enhancing efficiency and innovation but also prioritizes collaboration, diversity, and inclusion in building a strong organizational culture.